R. C. Blockley, The Fragmentary of Classicising Historians of the Later Roman Empire. Eunapius, Olimpiodorus, Priscus and Malchus (Area. Classical and Medieval Texts, Papers and Monographs published by Francis Cairns no 6; 10), Redwood Burn Ltd., Leeverpool 1981–1983, vol. I, ss. XII+196; vol. II, s. X+515 - Prostko-Prostyński, Jan (Balcanica Posnaniensia. Acta et studia, 1990)
Prostko-Prostyński Jan, book review: R. C. Blockley, The Fragmentary of Classicising Historians of the Later Roman Empire. Eunapius, Olimpiodorus, Priscus and Malchus(Area. Classical and Medieval Texts, Papers and Monographs published by Francis Cairns no 6; 10), Redwood Burn Ltd., Leeverpool 1981–1983, vol. I, ss. XII+196; vol. II, s. X+515, „Balcanica Posnaniensia. Acta et Studia” 1990, t. 5, s. 447–449.